Synthesis, Spectroscopic and Theoretical Studies of Some New Transition Metal Complexes with Mixed ligands Schiff Base and Bipyridyl - Al-Hamdani, Abbas Ali Salih; Al-dulyme, Nawres Khalid Gabraael (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The complexes Shiff base  and  mixed ligands complexes of bipyridyl and Schiff base 1,5-dimethyl-4-(5-oxohexan-2-ylideneamino)-2-phenyl-1H-pyrazol-3(2H)-one (L) with Cr(III), Mn(II), Fe(II) and Co(II) were prepared. The compounds have been characterized by FT-IR, UV-Vis, mass and 1H and 13C-NMR spectra, magnetic moment, elemental microanalyses (C.H.N.), chloride containing, atomic absorption and molar conductance. The studies made are indicating towards octahedral geometry for these complexes. Hyper Chem-8 program has been used to prediction structural geometries of compounds in gas state, the heat of formation, binding energy, total energy and electronic energy and dipole moment at 298oK. The compounds were also screened for their bioactive to antibacterial and antifungal.